Signs of Change? At‐Home and Breadwinner Parents' Housework and Child‐Care Time. Issue 2 (10th November 2016) - Chesley, Noelle; Flood, Sarah
Abstract: The authors analyze American Time Use Survey data to examine patterns in domestic work among at‐home and breadwinner parents to gauge how time availability, relative earnings, and gender shape time use in couples with extreme differences in earnings and work hours. They find that involvement in female‐typed housework is an important driver of overall housework time. It is counternormative housework behavior by at‐home fathers that shapes conclusions about how time availability, relative resources, and gender influence parents' housework. Although time availability appears to shape child care in comparable ways across parents, mothers are more engaged in child care than similarly situated fathers. Overall, comparisons point to the importance of distinguishing among gender‐normative housework tasks and accounting for differences in engagement on work and nonwork days. The results provide a basis for assessing the social significance of growing numbers of parents in work–family roles that are not gender normative.